OPENING AND ACTIVITIES OF THE KYRGYZ BRANCH OF THE USSR ACADEMY OF SCIENCES (1943-1950) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the prerequisites for the opening of the Kyrgyz branch of the USSR Academy of Sciences in Kyrgyzstan during the Great Patriotic War. Special attention is paid to the organizational work of KirFAN, as well as the study of its contribution to the development of Kyrgyz science and the formation of scientific personnel
Keywords: USSR Academy of Sciences, Kyrgyz branch, Council of People’s Commissars, Presidium, Council of People’s Commissars (SNK), CP (b) Central Committee, Great Patriotic War, decree, science, scientist, academician